Apprenticeship training and the business cycle - Mühlemann, Samuel [Verfasser]; Wolter, Stefan C. [Verfasser]; Wüest, Adrian [Verfasser] (My University, 2009)
"Dual apprenticeship training is a form of education at the upper secondary level, taking place in vocational school as well as in firms. Therefore, the willingness of firms to offer apprenticeships is a necessity for the functioning of this part of the educational system. Although it is likely that the economic climate has an impact on the firm's supply of apprenticeships, little is known so far about the impact of the business cycle on the number of apprenticeship programs offered. Using panel-data of Swiss cantons from 1988-2004, we find that the influence of the business cycle is statistically significant, but small in size. Instead, supply of apprenticeship programs is driven to a much greater extent by demographic change." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht als "IZA DP No. 4460", online zugänglich: http://edudoc.ch/record/37674/files/zu10024.pdf [Zugriff 4.6.2010]
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; T 1.3 Systematische Berufsbildungsforschung; I 2.2.1 Westeuropa; Berufsausbildung; Duales System; Konjunkturzyklus; Demografischer Wandel; Schülerzahl; Sekundäranalyse; 1988-2004; Schweiz